Green Synthesis of Silver Nanoparticles Using Areca Catechu L Peel Bioreductor as an Antibacterial Escherichia Coli and Staphylococcus Aureus - Restina Bemis; Frastica Deswardani; Heriyanti; Ratih Dyah Puspitasari; Nur Azizah (Indonesian Journal of Chemical Analysis (IJCA), 2023)
Areca nut or Areca catechu L is a plant that has many benefits, one of which is that it can be used as medicine. There are secondary metabolite compounds in betel nut. The presence of this secondary metabolite content makes the betel nut skin a high potential as a bioreductant to synthesize silver nanoparticles as an antibacterial. The process of synthesizing silver nanoparticles is carried out with the addition of a stabilizer in the form of Polyvinyl alcohol (PVA). The analysis results obtained using the UV-Vis instrument have wavelengths with variations in the addition of 1%, 3% and 5% PVA, respectively, are 448 nm, 456 nm and 460 nm. In the results of the analysis using XRD, the value of 2θ is silver nanoparticles (PVA 1%): 38,020; 43,930 ; 64,320 ; 77,270. silver nanoparticles (PVA 3%): 38,230; 44,270 ; 64,610 ; 77,500. And silver nanoparticles (PVA 5%) are 38,100 ; 44,240 ; 64,460 ; 77,370. For analysis using SEM, the particle size obtained with the help of the Imegej and OriginLab 8.5 applications, namely at AgNPS + PVA 1% is 28 nm - 31 nm. Agnps + PVA 3% ranged from 26 nm – 29 nm. And Agnps + PVA 5% has a size of 19 nm – 22 nm. For the results of FTIR data, the specific absorption peaks of Ag nanoparticles are located at frequencies of 412.23 cm-1, 453.57 cm-1, and 476.84 cm-1. Then in the antibacterial test, silver nanoparticles were used with the addition of 5% PVA. The size of the clear zone obtained in the test for E. coli bacteria is 11.2 mm and for S. Aureus it is 13 mm